Scientific production, collective health, and social determinants: A perspective from the humanities: Producción científica, salud colectiva y determinantes sociales: una perspectiva desde las humanidades - Acuña-Rodríguez, Mónica; Pérez-Arizabaleta, María del Mar; Cudris-Torres, Lorena; Duarte Arias, Daniel Augusto; Bolaño Acosta, Lilian Danielle; Gómez Campuzano, Martha Luz (Gaceta Médica de Caracas, 2026)
Collective health is a complex phenomenon shaped by social, cultural, economic, and psychological factors that go beyond traditional biomedical approaches. In this context, Humanities and Social Sciences (HSS) provide essential interpretive frameworks for understanding the social determinants of health and informing evidence-based public policies. This perspective article offers a critical reflection on HSS scientific production in Latin America, integrating regional and international literature with recent empirical evidence from Colombian universities. It argues that, although HSS research makes a substantial contribution to understanding well-being, mental health, and health promotion, its impact remains constrained by evaluation models that focus on traditional metrics. Strengthening more comprehensive and context-sensitive evaluation approaches is therefore essential to enhance HSS’s contribution to collective health and health equity in the region.